Outbreak of OXA-232-producing carbapenem-resistant Klebsiella pneumoniae ST15 in a Chinese teaching hospital: a molecular epidemiological study - Wu, Xiaoyan; Li, Xiangchen; Yu, Junjie; Shen, Mengli; Fan, Chenliang; Lu, Yewei; Gao, Junshun; Li, Xiaosi; Li, Hongsheng (Frontiers in Cellular and Infection Microbiology, 2023)
Background and Aims: Over the past five years, tThe incidence of OXA-232producing carbapenem-resistant Klebsiella pneumoniae (CRKP) has gradually increasedbeen on the rise in China over the past five years, potentially leading to nosocomial epidemics. The clonal propagation of the CRKP strain carrying blaOXA-232 can easily lead to nosocomial epidemics. Here, weThis study investigatesd the first outbreak of CRKP in the Second Affiliated Hospital of Jiaxing University. Methods: From Between February 2021 to and March 2022, 21 clinical isolates of OXA-232-producing CRKP were recovered from 16 patients in the Second Affiliated Hospital of Jiaxing University. We conducted The antimicrobial susceptibility testtests, whole genome sequencing, and bioinformatics were performed to determine the drug resistance profile of these clinical isolates.Results: Whole-genome sequencing indicated revealed that all 21 OXA-232-producing CRKP strains belonged to the sequence type 15 (ST15) and shared similar resistance, virulence genes, and plasmid types, suggesting the clonal spreading transmission between the environment and patients. Integrated genomic and epidemiological analysis traced the outbreak to two clonal transmission clusters, cluster 1 and cluster 2, including 14 and 2 patientss involving nine infections in ICU and four in brain surgery in cluster 1, and two in neurosurgery in cluster 2. It was speculated that the CRKP transmission mainly occurred in the ICU, followed by brain surgery, neurosurgery, and rehabilitation department. Phylogenetic analysiss revealed indicated that the earliest outbreak was might have started in the hospital for at least a year before the admission of the index patient, and these strains were closely related to those previously isolated from two major adjacent cities, Shanghai and Hangzhou. Comparative genomics showed that the IncFII-type and IncHI1B-type plasmids of cluster 2 had homologous recombination at the insertion sequence sites compared with the same type of plasmids of in cluster 1, resulting in the insertion of 4 new drug resistance genes, including TEM-1, APH(6)-Id, APH(3'')-Ib and sul2.Our study observed tThe clonal spread of ST15 OXA-232-producing clonal spread between patients and the hospital environment was observed. Our analysis demonstrates that integratingThe integration of genomic and epidemiological data can yield actionableoffers valuable insights and facilitate the control of nosocomial transmission.